Mitochondrial markers identify a genetic boundary of the Green Tiger Prawn (Penaeus semisulcatus) in the Indo-Pacific Ocean - Abdul Halim, Siti Amalia Aisyah; Othman, Ahmad Sofiman; Mohammed Akib, Noor Adelyna; Jamaludin, Noorul-Azliana; Esa, Yuzine; Mohd Nor, Siti Azizah (Biodiversity Research Center, Academia Sinica, 2021)
A population genetics study of the commercially important Green Tiger Prawn (Penaeus semisulcatus) was conducted in the Indo-Pacific Ocean with a focus on the Indo-Malay Archipelago waters of the South China Sea (SCS), Sulu Sea (SLS), Celebes Sea (CLS) and the Strait of Malacca (SOM), the latter being the main waterway that connects the Indian Ocean with the Pacific Ocean. A 548-base-pair region of mitochondrial COI and 571 base pairs of the control region (CR) were analysed in 284 specimens from 15 locations. Genetic divergences (Tamura 3-parameter) for COI ranged from 0.1% to 7.2% and CR 2.3% to 21.7%, with Bagan Pasir (BGP) in central SOM being the most genetically different from other populations (COI: 3.3–4.2%; CR: 7.1–16.5%). All populations were differentiated into two lineages with a genetic break in the vicinity of BGP; Lineage I comprised populations south of this site (SCS, SLS, CLS and part of SOM) and Lineage II comprised populations north of BGP (part of the SOM). Specifically, most individuals of Bagan Pasir (BGP) and another site just south of it, Batu Pahat (BPT), clustered in Lineage I, while all SOM populations to the north of these sites clustered in Lineage II. The BGP population is believed to be a mixed gene pool between the two lineages. The results could be attributed to the fluctuations of Pleistocene sea levels and a possible influence of the One Fathom Bank in SOM. High genetic diversity was recorded, π (Lineage I: COI: 3.4%; CR: 7.4%) (Lineage II: COI: 3.8%; CR: 12.6%) and, h (Lineage I: COI: 0.81; CR: 1.0) (Lineage II: COI: 0.57; CR: 0.99). Demographic statistics revealed that both lineages underwent a sudden expansion and consequent stabilisation in genetic variability. The findings of this study have wide implications for fisheries in the Indo-Pacific. The increased sampling effort within a narrower geographical scale by the current study permitted a precise locality of the genetic break for this species within the Indo-Pacific Ocean to be identified. The substantial genetic diversity within both lineages should be considered in fishery management and aquaculture development programs of this species in this region.